THE INFLUENCE OF STUDENTS’ MOTIVATION ON ENTREPRENEURSHIP ATTITUDE IN LIFE SKILLS PROGRAM - Rukanda, Nandang; Nurhayati, Sri; Ganda, Ganda (IKIP Siliwangi Bandung, 2020)
The research aims (1) To obtain an overview about the motivation of learners in their participation in the life skills program implemented, (2) To identify a clearly formulated life skills program so that it can be used as a measurable standard for determining entrepreneurship behavior, and (3) To describe an effort to improve learners’ motivation toward entrepreneurship behaviors in the life skills program, as required by the business and industry, which have beneficial impact on their daily economic life. This research uses a qualitative approach to uncover social phenomena that is intended to study the motivation and human behaviors in depth, instead of numbers. The techniques used to collect data in this research are observation, interview, and document study. The data analysis is done inductively starting from empirical facts. The underlying assumption of this study is that motivation has influence on entrepreneurship behavior of a person. The theories used in the study are the concept of entrepreneurship, community empowerment theory, the concept of nonformal education, and motivation theory. The results of the study show that the life skills program can motivate learners to develop entrepreneurship behavior and to make their own business as well.